2021
DOI: 10.3389/fgene.2021.721864
|View full text |Cite
|
Sign up to set email alerts
|

Physical and Functional Interaction of Mitochondrial Single-Stranded DNA-Binding Protein and the Catalytic Subunit of DNA Polymerase Gamma

Abstract: The maintenance of the mitochondrial genome depends on a suite of nucleus-encoded proteins, among which the catalytic subunit of the mitochondrial replicative DNA polymerase, Pol γα, plays a pivotal role. Mutations in the Pol γα-encoding gene, POLG, are a major cause of human mitochondrial disorders. Here we present a study of direct and functional interactions of Pol γα with the mitochondrial single-stranded DNA-binding protein (mtSSB). mtSSB coordinates the activity of the enzymes at the DNA replication fork… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 36 publications
1
6
1
Order By: Relevance
“…It also indicates there would always be sufficient Pol γ-β to function in association with Pol γ-α to form the dimeric holoenzyme in a 1:1 configuration for mtDNA replication, in agreement with previously published data [103] and with our speculations on additional roles for the fly Pol γ-β in mitochondrial RNA metabolism. Our data also contrast with data from human tissues, which indicates 2-to 3-fold excess of Pol γ-α over Pol γ-β [43]. PolG1 levels were higher than those of PolG2 (∼62%) only in the ovaries, a tissue that also has elevated relative expression of almost all mtDNA maintenance genes (Figure 2) due to the high levels of mtDNA replication and mitochondrial biogenesis that occur during oogenesis [104,105].…”
Section: Figure 2 Hierarchical Cluster Analysis Of the Relative Expre...contrasting
confidence: 99%
See 1 more Smart Citation
“…It also indicates there would always be sufficient Pol γ-β to function in association with Pol γ-α to form the dimeric holoenzyme in a 1:1 configuration for mtDNA replication, in agreement with previously published data [103] and with our speculations on additional roles for the fly Pol γ-β in mitochondrial RNA metabolism. Our data also contrast with data from human tissues, which indicates 2-to 3-fold excess of Pol γ-α over Pol γ-β [43]. PolG1 levels were higher than those of PolG2 (∼62%) only in the ovaries, a tissue that also has elevated relative expression of almost all mtDNA maintenance genes (Figure 2) due to the high levels of mtDNA replication and mitochondrial biogenesis that occur during oogenesis [104,105].…”
Section: Figure 2 Hierarchical Cluster Analysis Of the Relative Expre...contrasting
confidence: 99%
“…Another interesting fact about the Pol γ-mtSSB system is that, in humans, in vitro physical interactions between these two proteins appear to occur more prominently in the absence of the Pol γ-β dimer [43]. In addition, human Pol γ-α alone in vitro is an efficient gap-filling polymerase and in fact can participate in mtDNA repair [28].…”
Section: Mtdna Replication In Flies: the Best Studied Maintenance Pro...mentioning
confidence: 99%
“…In addition, our results showed that mtSSB decreased the T p ( f ) of the two mitochondrial holoenzymes at a concentration ten-fold lower than that of homologous EcoSSB, whereas noncognate gp2.5 had no significant effects on pause kinetics. These results support again that, even though no physical interactions have been described between Polγ-mtSSB (41), specific functional polymerase-SSB interactions could play a role in the modulation of the equilibrium between the moving and pause states characteristic of each polymerase.…”
Section: Discussionsupporting
confidence: 76%
“…These results indicate that species-specific interactions between the polymerase and the SSB may also play a role in the coordination of the polymerase and SSB activities at the fork and promotion of pause-free rate of strand displacement DNA synthesis. It is tempting to speculate that these interactions would be likely functional in the case of the mitochondrial polymerase-mtSSB system (41) and physical between the phage holoenzyme and the C-terminal tail of gp2.5 and EcoSSB (74,78). Noteworthy is that the specific interactions also seem to facilitate the inhibition of the pause-free rates of Polγexo- at high mtSSB concentration and tensions, showing the increased sensitivity of this variant to the cognate SSB.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation